Rare Metastatic Mesothelioma Occupying Intra-Atrial Cavity, Released by an Emergency Surgery: A Case Report and Literature Review - Takano, Tomohiro; Sato, Shuta; Ito, Ichiro; Yamamoto, Manabu; Tsukioka, Katsuaki; Matsumura, Yu; Kono, Tetsuya (Surgical Case Reports, 2025)
INTRODUCTION: Cardiac surgery for cardiovascular-associated mesothelioma has a poor prognosis. However, life-saving surgery is unavoidable to maintain circulation. This report describes a case in which metastatic intracardiac mesothelioma triggered sudden respiratory failure, which was reduced by surgical resection.CASE PRESENTATION: An 81-year-old man with a history of asbestos exposure presented to our hospital with sudden onset of dyspnea. Prior to this event, the pleura was involved in an epithelial malignancy, which was immunohistochemically negatively stained with anti-D2-40, WT-1, or anti-calretinin antibodies, which are positive markers of mesothelioma. Transthoracic echocardiography revealed a fragile and mobile tumor occupying the right atrium, and the patient was admitted for surgical tumorectomy. The operation was performed urgently using a cardiopulmonary bypass via a full sternotomy. The pericardium is grossly intact and does not adhere to the heart. A 3 × 5 cm tumor was tightly attached to the right atrium and was large enough to fit into the tricuspid valve. Therefore, the entire margin of the tumor stem attachment was resected from the lateral wall of the right atrium. Although the resected tumor was not positive for any of the three histopathological markers of mesothelioma, CDKN2A co-deletion revealed by fluorescence in situ hybridization led to a diagnosis of malignant mesothelioma.CONCLUSIONS: Surgical removal of intracardiac tumors that cause circulatory and respiratory instability is essential for the prevention of sudden death, regardless of prognostic determinants. This case demonstrates that mesotheliomas can metastasize to the endocardium. Even when nuclear atypia and negative results for immunohistochemical tests for the three mesothelioma markers suggest carcinoma, mesothelioma should still be considered and p16/CDKN2A co-deletion should be evaluated.